Management of Upper Extremity DVT - Zane, Kylie; Yu, Qian; Navuluri, Rakesh (Seminars in Interventional Radiology, 2025)
Upper extremity deep venous thrombosis (UEDVT) represents 4 to 11% of all deep vein thrombosis (DVT) and can result in persistent pain, swelling, and disability if inadequately treated. The range of presentations varies, from acute pain and swelling in the young overhead athlete to the asymptomatic cancer patient with chronic catheter-associated thrombus. Given the range of presentations, it is important to be familiar with the multimodal therapeutic options for UEDVT to appropriately select patients who will benefit from intervention. This is vitally important as use of central venous access devices and imaging increases, resulting in increased incidence and detection of UEDVT.
Keywords: Paget-Schroetter syndrome; upper extremity DVT; interventional radiology; thrombolysis